2011
DOI: 10.1073/pnas.1111957108
|View full text |Cite
|
Sign up to set email alerts
|

B-cell adaptor for PI3K (BCAP) negatively regulates Toll-like receptor signaling through activation of PI3K

Abstract: Toll-like receptors (TLRs) recognize pathogens and their components, thereby initiating immune responses to infectious organisms. TLR ligation leads to the activation of NF-κB and MAPKs through well-defined pathways, but it has remained unclear how TLR signaling activates PI3K, which provides an inhibitory pathway limiting TLR responses. Here, we show that the signaling adapter B-cell adaptor for PI3K (BCAP) links TLR signaling to PI3K activation. BCAP-deficient macrophages and mice are hyperresponsive to TLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 28 publications
10
108
0
1
Order By: Relevance
“…This hypothesis is further supported by the overlapping phenotype of BCAPdeficient and Lyn-deficient macrophages stimulated with TLR agonists. 21,68,94 However, this hypothesis remains to be experimentally tested.…”
Section: Future Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…This hypothesis is further supported by the overlapping phenotype of BCAPdeficient and Lyn-deficient macrophages stimulated with TLR agonists. 21,68,94 However, this hypothesis remains to be experimentally tested.…”
Section: Future Challengesmentioning
confidence: 99%
“…Critically, as is the case for BCAP mediated PI3K activation through BCR stimulation, tyrosine phosphorylation of BCAP is required for optimal restriction of inflammatory cytokine production, suggesting the requirement of tyrosine phosphorylation of BCAP for TLR mediated PI3K activation. 94 At present, the tyrosine kinase mediating BCAP phosphorylation in TLR-stimulated cells remains unknown. Notably, the SRC family kinase Lyn is implicated in phosphorylation of BCAP in B cells stimulated through their receptor or CD19 crosslinking.…”
Section: Future Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also shown that PI3 K is an endogenous suppressor of IL-12 production triggered by TLR signaling and limits excessive Th1 polarization. It is possible that crosstalk occurs between these three negative regulatory signaling pathways in TLR signaling (Troutman et al 2012;Ni et al 2012). Despite these strong immune responses, Leishmania persist in a latent form, which suggests a dynamic relationship between the host immune system and Leishmania that results in a balance between host survival and its control.…”
Section: Introductionmentioning
confidence: 99%